Experimental Evaluation of the Strut-and-Tie Model Applied to Deep Beam with Near-Load Openings (Journal of Engineering, 2017)
It is commonly known that Euler-Bernoulli’s thin beam theorem is not applicable whenever a nonlinear distribution of strain/stress occurs, such as in deep beams, or the stress distribution is discontinuous. In order to design the members experiencing such distorted stress regions, the Strut-and-Tie Model (STM) could be utilized. In this paper, experimental investigation of STM technique for three identical small-scale deep beams was conducted. The beams were simply supported and loaded statically with a concentrated load at the mid span of the beams. These deep beams had two symmetrical openings near the application point of loading. Both the deep beam, where the stress distribution cannot be assumed linear, and the existence of the openings, which causes stress discontinuity, make the use of Euler-Bernoulli’s thin beam theorem not applicable. An idealized STM for the beam was first established and then experimental test was carried out to study the capability of STM to deal with the distortion of stress caused by the presence of near-load openings in addition to the nonlinear distribution of stress occurring in deep beam. The test results showed that the beam designed using STM was able to withstand a load higher than the designed ultimate load. The service load, in the other hand, was within the range of the estimated one. The outcome of this study can then be added to the relatively few available experimental studies related to STM technique to enhance the validation of STM to efficiently treat different structural configurations where the linear stress assumption cannot be applied.